Lights on! A significant photoenhancement effect on ATRP by ambient laboratory light. Issue 4 (11th December 2015) - Zhang, Tao; Gieseler, Dan; Jordan, Rainer
Abstract : The influence of ambient laboratory light from common fluorescent lamps on AGET, ARGET, and classical ATRP reactions was investigated and significant differences were found except for ARGET ATRP. Abstract : Recently we reported on photoinduced ATRP using a household fluorescent lamp as the light source (T. Zhang, et al., Polym. Chem., 2014, 5, 4790). Results implied that typical laboratory light might have a considerable impact on the ATRP reaction as fluorescent lamps are commonly used for ceiling and fume hood illumination. Here, we show the influence of ambient laboratory light on AGET, ARGET, and classical ATRP reactions. Except for ARGET ATRP, for all other ATRP types a significant photoenhancement effect by light originating only from fluorescent lamps was observed. A standard fume hood illumination caused the strongest influence.